Caracterização métrica e gramática de restrições do acento verbal no português brasileiro - Rezende, Fernanda Alvarenga (2018)
The main objective of this study was to deal with the stress and proposes a new description of Brazilian Portuguese (BP) verbs through the Optimality Theory (OT) constraints model and the Metrical Phonology insights (HAYES, 1995). In order to do so, we had Magalhães (2004) non-verb analysis as guiding principle. Specifically, this study aimed: to make a link between phonology and morphology through phonological and morphological constraints and to propose a stress-related constraints grammar to BP verb system. For metrical assignment, we based this study on the Parametric Metrical Theory (HAYES, 1995) to formulate three parameters related to the primary stress of BP verbs: the first refers to the foot construction and requires the formation of a non-iterative syllabic trochee from right to left and degenerate feet are allowed only in the strong position, when the canonical foot cannot be formed (weak prohibition); the second deals with extrametricality and, depending on the person’s verb and the verb tense, can reach the final syllable or the final consonant, in this case, N or S. The third parameter requires that the End Rule be on the right. In this proposal, we consider that the verbs’canonical foot is the syllabic trochee, which excludes the relevance of syllable quantity to the stress assignment in this lexical category. In the OT analysis, we captured the facts related to the BP verb stress with this hierarchy: ALIGN-SUFFIX(Future), ALIGN-THEME, *FINALITY(Present) >> RIGHTMOST, TROCHEE >> SNONFINALITY >> PrWd-RIGHT >> FTBIN, PARSE-σ. In sum, we concluded that: the alignment constraints were fundamental to demonstrate the morphology-phonology interface, as they ensure that the stress location occurs in the morphological context suited to the verb tense that we analyzed; every verb tense has its predictable stress, therefore the syllable quantity does not matter to the stress assignment, but rather the morphological context; the extrametricality is necessary to the analysis and can reach a segment or an entire syllable, according to the second parameter that we presented; there is only one stress rule, only the application domain changes; and considering verbs and non-verbs, we can suppose that PB is a partially quantity-sensitive language, as these two lexical categories have different behaviors when considering the syllabic constitution in the stress assignment.